Dietary Emulsifier Sodium Stearoyl Lactylate Alters Gut Microbiota in vitro and Inhibits Bacterial Butyrate Producers - Elmén, Lisa; Zlamal, Jaime E.; Scott, David A.; Lee, Ryan B.; Chen, Daniel J.; Colas, Alexandre R.; Rodionov, Dmitry A.; Peterson, Scott N. (Frontiers in Microbiology, 2020)
Dietary emulsifiers are widely used in industrially processed foods, although the effects of these food additives on human gut microbiota are not well studied. Here, we investigated the effects of five different emulsifiers (glycerol monoacetate, glycerol monostearate, glycerol monooleate, propylene glycol monostearate and sodium stearoyl lactylate) on fecal microbiota in vitro. We found that <0.025% (w/v) of sodium stearoyl lactylate (SSL) reduced the relative abundance of the bacterial class, Clostridia and others. The relative abundance of the families Clostridiaceae, Lachnospiraceae and Ruminococcaceae was substantially reduced whereas that of Bacteroidaceae and Enterobacteriaceae was increased. Given the marked impact of SSL on Clostridia, we used genome reconstruction to predict community-wide production of short-chain fatty acids, which were experimentally assessed by GC-MS analysis. SSL significantly reduced concentrations of butyrate, and increased concentrations of propionate compared to control cultures. The presence of SSL increased amounts of LPS and flagellin in cultured communities, thereby enhancing the proinflammatory potential of SSL-selected bacterial communities.